2014
DOI: 10.1016/j.peptides.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Membrane binding and oligomer membrane insertion are necessary but insufficient for Bacillus thuringiensis Cyt1Aa toxicity

Abstract: Bacillus thuringiensis Cyt proteins are pore-forming toxins that have insecticidal activity mainly against dipteran insects. However, certain Cyt proteins have toxicity to some insect orders, but not toxicity of Cyt1Aa against lepidopteran larvae has been found. Insect specificity has been proposed to rely in specific binding to certain lipids on the brush border membrane of midgut cells since no protein receptors have been described so far. To determine the molecular basis of Cyt1Aa insect specificity we comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(44 reference statements)
1
9
0
Order By: Relevance
“…preventing their fall-off into arciform oligomers. At present, we can nonetheless propose a model that fits all the information developed by us and others on Cyt1Aa pore formation [2][3][4][5][6]21,27,31,36 (Supplementary Fig. 16).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…preventing their fall-off into arciform oligomers. At present, we can nonetheless propose a model that fits all the information developed by us and others on Cyt1Aa pore formation [2][3][4][5][6]21,27,31,36 (Supplementary Fig. 16).…”
Section: Discussionsupporting
confidence: 59%
“…It remains uncertain whether or not the mosquito gut is a reducing environment 19 and thus under what form the protoxin is mainly released upon crystal dissolution in the natural context. We found that regardless of whether the protoxin is present in the form of a disulfide-bridged dimer or a protoxin monomer, addition of proteinase K, shown to faithfully mimic mosquito gut proteases 20 , allows activation into a 23 kDa toxin monomer, consistent with the cleavage of its first 30 and last 5 amino acids 21 ( Fig. 4b and Supplementary Fig.…”
Section: And Supplementarymentioning
confidence: 77%
See 2 more Smart Citations
“…These strains of recombinant spore-crystals were grown in Embrapa medium [ 35 ], supplemented with 6 μg mL −1 of chloramphenicol [ 36 ] for BtCry1Ba6 and BtCry10Aa, with 10 μg mL −1 erythromycin [ 37 , 38 ] for BtCry1Ia, incubated for 72 h at 28 °C, and maintained in a shaker. After growing, these were centrifuged at 12,800 × g for 30 min at 4 °C, frozen for 16 h and then lyophilized for 18 h. The colony forming units test (CFU) was carried out to quantify the viable Bt spore-crystals and followed the protocol proposed by Alves and Moraes [ 39 ].…”
Section: Methodsmentioning
confidence: 99%